NIAID-Sponsored 2010 Guidelines for Managing Food Allergy: Applications in the Pediatric Population - Burks, A. Wesley (American Academy of Pediatrics, 2011)
Data from many studies have suggested a rise in the prevalence of food allergies during the past 10 to 20 years. Currently, no curative treatments for food allergy exist, and there are no effective means of preventing the disease. Management of food allergy involves strict avoidance of the allergen in the patient's diet and treatment of symptoms as they arise. Because diagnosis and management of the disease can vary between clinical practice settings, the National Institute of Allergy and Infectious Diseases (NIAID) sponsored development of clinical guidelines for the diagnosis and management of food allergy. The guidelines establish consensus and consistency in definitions, diagnostic criteria, and management practices. They also provide concise recommendations on how to diagnose and manage food allergy and treat acute food allergy reactions. The original guidelines encompass practices relevant to patients of all ages, but food allergy presents unique and specific concerns for infants, children, and teenagers. To focus on those concerns, we describe here the guidelines most pertinent to the pediatric population.